Mengukur Kapabilitas Teknologi Industri Kecil Batik (Studi Kasus Batik Komar Bandung) - Retno Indriartiningtias (Performa: Media Ilmiah Teknik Industri, 2010)
Batik Komar is one of a famous Batik’s Small Industries in West Java. As a Small Industries, Batik Komar has to survive in the competitive. One mission of batik Komar is to make Batik knowing in the world. To meet that mission, Batik Komar has to compose their strategy specially in technology strategy. This research aim is to develop technology strategy using technometric model. By using technometric model, the contribution of each technological component can be conducted as complement to overcome weakness of performance assessment at this time. From the research component with the highest contribution intensity is humanware, and then orgaware, infoware and technoware. The technology contribution coefficient value (TCC) of Batik Komar is medium. It show that Batik Komar has enough technology contribution.